Mir‐302c mediates influenza A virus‐induced IFNβ expression by targeting NF‐κB inducing kinase. Issue 24 (19th November 2015) - Gui, Shulin; Chen, Xueyuan; Zhang, Mo; Zhao, Fanpeng; Wan, Yushun; Wang, Li; Xu, Gang; Zhou, Li; Yue, Xin; Zhu, Ying; Liu, Shi
Abstract : Little is known about the role of microRNA during influenza A virus (IAV) infection. We observed that NIK 3′UTR luciferase activity was elevated during IAV infection. Further studies demonstrated that miR‐302c reduced NIK expression, resulting in the reduction of IFNβ mRNA expression. We found that miR‐302c prevented the translocation of NF‐κB from the cytosol to the nucleus. Furthermore, IAV infection downregulated miR‐302c expression, leading to the activation of IFNβ expression and the inhibition of viral replication. Compared to miR‐302c, miR‐520e cannot promote viral replication and production, although the two microRNAs target the same site of the NIK 3′UTR. Collectively, our work defines a novel signaling pathway implicated in the control of IFNβ mRNA expression during IAV infection. Abstract : A novel signaling pathway implicated in the control of IFNβ mRNA expression during IAV infection. IAV infection induces IFNβ mRNA expression by downregulating miR‐302c expression. MiR‐302c inhibits IFNβ expression by directly targeting the 3′UTR of NIK.